INTERNALIZATION CHARACTER EDUCATION IN STUDENTS ELEMENTARY SCHOOL THROUGH THE STORY OF CHILDREN - Sri Widayati; Elizar Elizar (University of Sang Bumi Ruwa Jurai, 2017)
One way to form elementary school students is to characterize the school environment, through literary learning (children's stories). Children's stories have a very fundamental role in character education. Children's stories can be used as teaching materials to form good characters for elementary students. Therefore, this study aims to determine the value of character education contained in the collection of children's stories on Peci and KKPK. To know this case in this research used qualitative descriptive method. The results of this study indicate that children's stories contained in Peci and KKPK can be used as teaching material because it has the value of character education as desired by the curriculum 2013. In addition, Peci and KKPK also have a story appropriate to the contextual life of children so that elementary students will be easy to internalize These values at once realize in everyday life.